PENGARUH JUMLAH PENDUDUK DAN BELANJA TIDAK LANGSUNG TERHADAP KEMISKINAN DI KABUPATEN ACEH TIMUR - Ria Afrida; Umaruddin Usman; Tarmizi Abbas (Jurnal Ekonomi Regional Unimal, 2021)
This study examined the Influence of Population and Indirect Expenditure on Poverty in the East Aceh Regency. This study used secondary data during 2006-2019. The model used was multiple linear regression. The results partially showed that the population and expenditure did not have a direct and significant negative effect on poverty in East Aceh Regency. Simultaneously, the Population and Indirect Expenditure positively and significantly influenced poverty in East Aceh Regency. The effects of population and indirect expenditure on poverty were 94.23%, while the rest was influenced by other variables of 5.77% outside this model.